The relevance of the church's involvement in the protection of children and adolescents in the city of Londrina - Molina, Marlene Rocha; Nascimento, Oslei do; Ribeiro, Sérgio Adriano; Magalhães, Leandro Henrique (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Teologia, 2022)
The present work addresses the role of the evangelical church, the body of christ, in the issue of the rights of children in situations of social lack, as well as its consequences in society. a field research was carried out with 59 evangelical christians of different denominations, in which a small sample of the level of involvement of this public in social causes in favor of children and adolescents at social risk, as well as biblical understanding about this, was extracted. the work points out a history of advances regarding the rights and situation of children and adolescents in brazil nowadays, and how the church can contribute to the ills of society for the children and adolescents. it shows the urgent need for religious intervention in this cause, as the church is sought by society as a safe host for these demands.